The Effect of Sniper Game on Throwing Accuracy in Elementary School Physical Education - Austein Septi Dwi Maharani; Rahmat Permana; Anggia Suci Pratiwi (BASICA, 2026)
This study aimed to examine the effect of the sniper game on throwing accuracy in Physical Education, Sports, and Health (PJOK) learning among fifth-grade elementary school students. The sniper game is a target-based, play-oriented activity designed to enhance manipulative motor skills, particularly throwing accuracy. A quasi-experimental design with a pretest–posttest control group model was employed. The participants were 30 fifth-grade students of SDN 3 Sukamenak, divided into an experimental group (n = 15) and a control group (n = 15). The experimental group received PJOK instruction using the Sniper game, while the control group received conventional instruction. Data were collected through a throwing accuracy test and analyzed using descriptive statistics and paired sample t-tests at a significance level of 0.05.The results showed improvements in both groups; however, the experimental group demonstrated a greater increase in mean scores (Δ = 1.267) compared to the control group (Δ = 0.667). Statistical analysis indicated a significant effect of the sniper game on throwing accuracy (p < 0.05). These findings demonstrate that the sniper game can be effectively implemented as a game-based instructional strategy to improve throwing accuracy in elementary school PJOK learning. The scope of this study was limited to throwing accuracy; future research may explore its broader impact on other manipulative motor skills and across different educational contexts.